2003
DOI: 10.1007/s00104-002-0595-1
|View full text |Cite
|
Sign up to set email alerts
|

Deszendierende intramedulläre Nagelung zur Behandlung dislozierter suprakondylärer Oberarmfrakturen im Kindesalter

Abstract: As soft tissue swelling does not hinder the surgeon, ESIN shows a high rate of closed stabilizations. No cast has to be applied and free ROM can be permitted for all patients. Avoidance of iatrogenic lesions of the n. ulnaris and secondary displacements are other advantages of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…During fracture fixation, the descending ulnar nail perforated the distal corticalis and injured the nerve. 2 studies have not found any ulnar nerve injuries using the ESIN technique in 110 patients in total (Weinberg et al 2003, Schaffer et al 2007). Considering the rates of ulnar nerve injuries, these results together with ours confirm the superiority of ESIN for treatment of displaced supracondylar fractures.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…During fracture fixation, the descending ulnar nail perforated the distal corticalis and injured the nerve. 2 studies have not found any ulnar nerve injuries using the ESIN technique in 110 patients in total (Weinberg et al 2003, Schaffer et al 2007). Considering the rates of ulnar nerve injuries, these results together with ours confirm the superiority of ESIN for treatment of displaced supracondylar fractures.…”
Section: Discussionmentioning
confidence: 97%
“…Skaggs et al (2004) have described a series of supracondylar fractures with parallel radial stabilization using 2 or 3 pins. While elastic stable intramedullary nailing (ESIN) has become the gold standard for treatment of long bone fractures of the upper and lower limb (Schalamon and Petnehazy 2009), there are few reports on use of the ESIN technique for treatment of supracondylar fractures (Prevot et al 1990, Weinberg et al 2003, Schaffer et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zahlreiche Artikel diskutieren die chirurgischen Versorgungsmöglichkeiten von kindlichen suprakondylären Humerusfrakturen [1-3, 6,7,[12][13][14][15] …”
Section: Chirurgische Versorgungunclassified